1976
DOI: 10.1002/j.1879-3479.1976.tb00585.x
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Work Capacity of the Expectant Mother and Its Effect on Pregnancy, Labor and the Newborn

Abstract: 149 healthy primigravidae participated in the study dealing with the correlation between the physical work capacity of the mother and the course of pregnancy and labor and the possible influence of physical work capacity on the development of the fetus and placenta. 62 of the mothers were followed prospectively from the end of the first trimester and their physical work capacity was determined on two occasions prior to the 38th week of the pregnancy. All mothers were examined during the 38th week. Physical wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…Good physical condition during pregnancy has been suggested to have a beneficial effect on reproductive performance (Erkkola 1976). In certain clinical situations, when the fetus is compromised in utero, strenuous exercise may be harmful to fetoplacental well-being (Hon & Wohlgemuth 196 1).…”
mentioning
confidence: 99%
“…Good physical condition during pregnancy has been suggested to have a beneficial effect on reproductive performance (Erkkola 1976). In certain clinical situations, when the fetus is compromised in utero, strenuous exercise may be harmful to fetoplacental well-being (Hon & Wohlgemuth 196 1).…”
mentioning
confidence: 99%
“…The implication that maternal exercise leads to poor fetal outcome has not been supported through the work of several other researchers, however. Erkkola (1976) and Wong and McKenzie (1987) found that women with higher physical work capacities had newborns with slightly higher birth weights. Hall and Kaufmann (1987) found that women who exercised at high intensities had newborns of slightly higher birth weights and had significantly fewer cesarean deliveries.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Macphail et al, 2000, tapiz rodante (Clapp, 1989), natación o actividades acuáticas (Sibley et al, 1981. Del castillo, 2002 o simplemente "variedad de actividades físicas de tiempo libre" (Berkowitz et al, 1983. Erkkola, 1976.…”
Section: Tipo De Clasesunclassified